2002
DOI: 10.1103/physrevlett.88.046101
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Mediated Heteroepitaxy versus Homoepitaxy: Kinetics for Group-IV Adatoms on As-Passivated Si(111) and Ge(111)

Abstract: Using ab initio calculations we have determined the paths and activation energies for diffusion of group-IV atoms (Si, Ge, and Sn) on top of the As layer on As-passivated Si(111), and for exchange with an As atom. The kinetics of Si, Ge, and Sn adatoms is substantially different: Si adatoms are readily incorporated under the As layer. Ge adatoms diffuse far on top of the As layer and can reach existing steps. We show for the first time that the ratio between diffusion and exchange barriers depends strongly on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Thus it can easily be imagined that the reactivity of the step edges is reduced in the same way as by the As coverage of the Si͑111͒ terraces: In our previous calculations, 37 we have shown that for Ge atoms deposited on Si͑111͒:As surfaces the barrier for incorporation under the As layer is about three times as large as the diffusion barrier on top of the As layer. This is in line with the speculation of Kaxiras [15][16][17] concerning the reduced incorporation probability at step edges due to surfactant atoms, especially for Ge adatoms in heteroepitaxy.…”
Section: Incorporated As Atomsmentioning
confidence: 99%
“…Thus it can easily be imagined that the reactivity of the step edges is reduced in the same way as by the As coverage of the Si͑111͒ terraces: In our previous calculations, 37 we have shown that for Ge atoms deposited on Si͑111͒:As surfaces the barrier for incorporation under the As layer is about three times as large as the diffusion barrier on top of the As layer. This is in line with the speculation of Kaxiras [15][16][17] concerning the reduced incorporation probability at step edges due to surfactant atoms, especially for Ge adatoms in heteroepitaxy.…”
Section: Incorporated As Atomsmentioning
confidence: 99%
“…This points to another kinetic limitation identified in SME, in particular, to a slow exchange/deexchange process by which the Ge atoms diffusing on top of a surfactant layer incorporate into the growing Ge layer below the surfactant and vice versa. 16,17 Top facets of the 3D islands show a ͱ3ϫͱ3 structure with Ϸ1 Å high undulations indicating the presence of a strain relieving dislocation network in the Ge/Si interface underlying the islands ͓Fig. 1͑c͔͒.…”
mentioning
confidence: 99%
“…3 An alternative approach is the use of surfactants that change the surface energy and surface kinetics, thus suppressing the three-dimensional island formation and establishing a layer by layer growth mode. [4][5][6][7][8][9][10][11][12] Surfactant mediated epitaxy (SME) also has the advantage that atomically sharp interfaces can be achieved. In addition, the defect structure of Ge films grown on Si(111) can be drastically improved by employing SME: The lattice mismatch of 4.2 % is accomodated by the formation of a periodic network of interfacial misfit dislocations.…”
Section: Institute Of Laser and Plasma Physics University Of Duisburmentioning
confidence: 99%